The Qur'anic Miraculousness Concerning the Expulsion of the Jews from the Holy Land (The Scientific Journal of University of Saba Region, 2025)
This study is aimed at highlighting some aspects of the miraculous nature of the Glorious Qur,an, particularly the unseen, rhetorical, and numerical miraculousness regarding the expulsion of the Jews from the Holy Land. The study relies on Surah Al-Isra, which includes references to this subject, and shows that this event is miraculous due to the Quran,s foretelling of it before its occurrence, in accordance with what was witnessed in historical happenings and consecutive events. The study presents a comprehensive analysis about miraculousness of the Glorious Qur,an regarding the expulsion of the Jews from the Holy Land. It defines the unseen miraculousness, highlights its significance, and presents relevant examples. It further examines the rhetorical miraculousness, clarifies meanings of the verses, vocabulary, and offers a summary of their meanings. It also analyzes the numerical miraculousness regarding this subject. The study concludes with several findings: the expulsion of the Jews from the Holy Land is mentioned in the Glorious Quran in unequivocal and assertive terms, which indicates that it will be an inevitable and decisive matter, and it will be carried out by the people of the Qur,an. This is confirmed by the Glorious Qur,an in all its miraculous dimensions. The appropriate interpretation of this subject is the interpretation that touches reality and resolves its problems. The Quran,s advance mention of this event exemplifies a facet of the unseen miraculousness in the Glorious Qur,an, as well as the rhetorical and numerical miraculousness.
Keywords: The Glorious Qur'an; Surah Al-Isra; unseen miraculousness; rhetorical miraculousness; numerical miraculousness; Jews